2018
DOI: 10.1007/s40502-018-0363-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive physiological and biochemical response of sugarcane genotypes to high-temperature stress

Abstract: Impact of elevated temperature on physiological and biochemical changes were evaluated in 5 commercial sugarcane genotypes and 2 wild species clones at two different growth phases. The study revealed that heat stress decreased chlorophyll content, chlorophyll stability index (CSI), SPAD value, maximum quantum efficiency of PSII photochemistry (Fv/Fm ratio), leaf gas exchange parameters, relative water content (RWC), and activities of nitrate reductase (NR), sucrose-metabolizing enzymes (SPS, SS, AI, NI) in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…In the present investigation, heat stress obviously induced a marked accumulation of proline compared to the control (Table 3). Such obtained results are concomitant with those reported by [95] on rice and [96] on sugar cane. The accumulation of proline under heat stress could also serve as chaperones, stabilizing and protecting the structure of enzymes and proteins, maintaining membrane integrity and scavenging ROS, and as nitrogen and carbon pools [96,97].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present investigation, heat stress obviously induced a marked accumulation of proline compared to the control (Table 3). Such obtained results are concomitant with those reported by [95] on rice and [96] on sugar cane. The accumulation of proline under heat stress could also serve as chaperones, stabilizing and protecting the structure of enzymes and proteins, maintaining membrane integrity and scavenging ROS, and as nitrogen and carbon pools [96,97].…”
Section: Discussionsupporting
confidence: 91%
“…Such obtained results are concomitant with those reported by [95] on rice and [96] on sugar cane. The accumulation of proline under heat stress could also serve as chaperones, stabilizing and protecting the structure of enzymes and proteins, maintaining membrane integrity and scavenging ROS, and as nitrogen and carbon pools [96,97]. Pretreatment of wheat with K 2 SiO 3 and SiO 2 NPs alleviated the adverse effects of heat stress via increasing photosynthetic pigments and organic solutes, including soluble sugars, sucrose, and proline content (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…In our previous studies on oxidative [ 16 ], heat [ 18 ] and drought stresses [ 19 ], higher CF were observed in the wild species than that in the cultivated sugarcane under oxidative stress. The prolinecontent was 69 and 16.6% higher in S.Spontaneum and Erianthus sp., respectively, compared with those in their respective controls.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of photosynthetic pigments is decreased by heat shock. Heat tolerance is directly correlated with plant's capacity to sustain the rates of CO2 uptake and leaf gas exchange under heat stress (Kohila and Gomathi, 2018). Further, heat stress significantly affects leaf water efficiency, stomatal conductance, and intercellular CO2 concentration.…”
Section: Photosynthesismentioning
confidence: 99%